\(\frac{2}{3}\)x2-\(\frac{1}{2}\)y)3 (3x2
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 11 2017

) \(\dfrac{x^3+8y^3}{2y+x}\)

\(=\dfrac{x^3+\left(2y\right)^3}{x+2y}\)

\(=\dfrac{\left(x+2y\right)\left[x^2+x.2y+\left(2y\right)^2\right]}{x+2y}\)

\(=x^2+2xy+4y^2\)

b) \(\dfrac{a-1}{2\left(a-4\right)}+\dfrac{a}{a-4}\) MTC: \(2\left(a-4\right)\)

\(=\dfrac{a-1}{2\left(a-4\right)}+\dfrac{2a}{2\left(a-4\right)}\)

\(=\dfrac{a-1+2a}{2\left(a-4\right)}\)

\(=\dfrac{3a-1}{2\left(a-4\right)}\)

c) \(\dfrac{x^3+3x^2y+3xy^2+y^3}{2x+2y}\)

\(=\dfrac{\left(x+y\right)^3}{2\left(x+y\right)}\)

\(=\dfrac{\left(x+y\right)^2}{2}\)

d) \(\left(x-5\right)^2+\left(7-x\right)\left(x+2\right)\)

\(=\left(x^2-2.x.5+5^2\right)+\left(7x+14-x^2-2x\right)\)

\(=x^2-10x+25+7x+14-x^2-2x\)

\(=39-5x\)

e) \(\dfrac{3x}{x-2}-\dfrac{2x+1}{2-x}\)

\(=\dfrac{3x}{x-2}+\dfrac{2x+1}{x-2}\)

\(=\dfrac{3x+2x+1}{x-2}\)

\(=\dfrac{5x+1}{x-2}\)

h) \(\dfrac{1}{3x-2}-\dfrac{1}{3x+2}-\dfrac{3x+6}{4-9x^2}\)

\(=\dfrac{1}{3x-2}-\dfrac{1}{3x+2}+\dfrac{3x+6}{9x^2-4}\)

\(=\dfrac{1}{3x-2}-\dfrac{1}{3x+2}+\dfrac{3x+6}{\left(3x-2\right)\left(3x+2\right)}\) MTC: \(\left(3x-2\right)\left(3x+2\right)\)

\(=\dfrac{3x+2}{\left(3x-2\right)\left(3x+2\right)}-\dfrac{3x-2}{\left(3x-2\right)\left(3x+2\right)}+\dfrac{3x+6}{\left(3x-2\right)\left(3x+2\right)}\)

\(=\dfrac{\left(3x+2\right)-\left(3x-2\right)+\left(3x+6\right)}{\left(3x-2\right)\left(3x+2\right)}\)

\(=\dfrac{3x+2-3x+2+3x+6}{\left(3x-2\right)\left(3x+2\right)}\)

\(=\dfrac{3x+10}{\left(3x-2\right)\left(3x+2\right)}\)

27 tháng 11 2017

câu f ,g đâu

10 tháng 3 2020

\(a.\left(x^2+\frac{2}{5}y\right)\left(x^2-\frac{2}{5}y\right)\\ =x^4-\frac{4}{25}y^2\)

\(b.\left(2x+y^2\right)^3\\ =8x^3+12x^2y^2+6xy^4+y^6\)

\(c.\left(3x^2-2y\right)^3\\ =27x^6-54x^4y+36x^2y^2-8y^3\)

\(\left(x+4\right)\left(x^2-4x+16\right)\\ =x^3+64\)

\(e.\left(x^2-\frac{1}{3}\right)\left(x^4+\frac{1}{3}x^2+\frac{1}{9}\right)\\ =x^6-\frac{1}{27}\)

10 tháng 3 2020

thansk

10 tháng 7 2019

\(1,\left(\frac{a}{3}+4y\right)^2=\frac{a^2}{9}+\frac{8ay}{3}+16y^2\)

\(2,\)Bạn xem lại đề bài giùm mk nhé

\(\left(x^2+\frac{2}{5}y\right).\left(x^2-\frac{2}{5}y\right)=\left(x^2\right)^2-\left(\frac{2}{5}y\right)^2=x^4-\frac{4}{25}y^2\)